Analisis Fikih Muamalah terhadap Sewa Ruko yang Belum Dibangun - Krisna Aditia Putra; Fauziah, Eva; Zia Firdaus Nuzula (UNISBA Press, 2024)
Abstract. Regarding the object of study discussed, this thesis examines the practice of renting out shops (ruko) that have not yet been built in Desa Sukajaya, Kecamatan Lembang, Kabupaten Bandung Barat. In its implementation, the shop owner rents out the ruko to tenants for use or benefit, while the tenant provides money or compensation for the benefit received. The ruko has not yet been built, but the owner has already rented it out. The issue that arises is that the rental object does not exist at the time the contract is made. To analyze the data, the author uses a descriptive-analytical method. The type of research applied is field research. From the results of the presentations conducted, the author found: The practice of renting out shops in Desa Sukajaya, Kecamatan Lembang, Kabupaten Bandung Barat, is permissible according to Islamic law. Based on the views of Hanafiyah, Malikiyah, and Hanabilah, ijarah can be linked to a future period. This is because the ijarah contract takes effect gradually, in line with the emergence of ma'qud 'alaih, which is the benefit. Thus, the ijarah contract is essentially linked to the time when the benefit exists. In the case of renting out shops in Desa Sukajaya, the rented shops will be handed over at a time agreed upon by both parties, due to the nature of ijarah that applies gradually as the benefit of the shop emerges. Abstrak. Kajian ini mengupas tentang praktik sewa-menyewa ruko yang belum dibangun di Desa Sukajaya Kecamatan Lembang Kabupaten bandung Barat. Dalam pelaksanaannya, pemilik ruko menyewakan rukonya kepada penyewa untuk digunakan atau dimanfaatkan, sementara penyewa memberikan uang atau imbalan atas manfaat tersebut. Ruko tersebut masih belum dibangun, tetapi pemilik sudah menyewakannya. Hal ini memunculkan pertanyaan terkait praktik sewa-menyewa ruko yang belum dibangun dan tinjauan Fikih Muamalah terhadap praktik tersebut. Data dianalisis menggunakan metode deskriptif-analitis. Jenis penelitian yang diterapkan adalah penelitian lapangan (field research). Hasil penelitian menunjukan bahwa Praktik sewa ruko di Desa Sukajaya Kecamatan Lembang Kabupaten Bandung Barat, menurut Fikih Muamalah diperbolehkan, berdasarkan pandangan Hanafiyah, Malikiyah, dan Hanabilah, ijarah boleh disandarkan pada waktu yang akan datang. Hal ini karena akad ijarah berlaku secara bertahap, sesuai dengan munculnya ma'qud 'alaih, yaitu manfaat. Dengan demikian, akad ijarah sebenarnya disandarkan pada saat manfaat ada. Dalam hal sewa ruko di Desa Sukajaya, ruko yang disewakan akan diserahterimakan pada waktu yang telah disepakati oleh kedua belah pihak, karena sifat ijarah yang berlaku bertahap sesuai dengan munculnya manfaat ruko tersebut.